Prevalence, risk factors, and hematologic changes in dogs from Baja California with presence of Ehrlichia spp., and coinfection with Anaplasma spp. - López-Valencia, Gilberto; Meza-Silva, Katya Monserrat; Haro-Álvarez, Ana Paulina; Trasviña-Muñoz, Enrique; Garcia-Reynoso, Issa Carolina; Herrera-Ramírez, José Carlomán; Gómez-Gómez, Sergio Daniel (Austral Journal of Veterinary Sciences, 2024)
Ehrlichia and Anaplasma are obligate intracellular, gram-negative bacteria with tropism for hematopoietic cells, especially leukocytes and platelets. There are several Ehrlichia species that infect dogs. Ehrlichia canis is transmitted by Rhipicephalus sanguineus and replicates within monocytes and macrophages, leading to canine monocytic ehrlichiosis, a disease of worldwide distribution. The clinical signs are varied and non-specific. Anaplasma has two species that infect dogs, Anaplasma phagocytophilum and Anaplasma platys, the second also transmitted by Rhipicephalus sanguineus. This study aimed to evaluate the epidemiology and hematologic changes associated with the presence of Ehrlichia spp. And Anaplasma spp. coinfection in dogs from Baja California. Complete hematological analysis, examination of buffy coat smears, and ELISA tests were performed on blood samples from three veterinary diagnostic laboratories from Mexicali and Tijuana cities in Baja California, Mexico. A total of 5,469 dog samples were analyzed. The overall prevalence of Ehrlichia spp., was 4.79%, with a distribution of 6.3% in Mexicali (OR: 2.39 CI: 1.69-3.17) and 2.5% in Tijuana. The peak of infection was found in September. Contact with other dogs and tick infestation were the risk factors associated with infection (P < 0.05). There was 96% co-infection only in Tijuana and 0% in Mexicali. Anemia, thrombocytopenia, and hyperproteinemia are associated with Ehrlichia spp., and Ehrlichia/Anaplasma infection. In view of the foregoing, we have to maintain epidemiologic vigilance, as well as look further into the ticks present in the state and the possibility of transmission of unusual pathogens.